Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/bf03353787
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Palladium Supported on Ferric Oxide Nano-catalysts for Carbon Monoxide Oxidation in Low Temperature

Abstract: Catalytic property of Pd/Fe2O3 catalysts on carbon monoxide (CO) oxidation at low temperature were investigated in this paper. Both the as-prepared and H2-pretreated Pd/Fe2O3 catalysts show catalytic performances on CO oxidation. The CO was completely converted at 333 K for the as-prepared sample, whereas at 313 K for H2-pretreated Pd/Fe2O3-573 catalyst. The catalytic performance of the Pd/Fe2O3 catalyst decreases with increased calcination temperature. This may be due to the increased crystallinity of the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The first negative peaks observed in Figure 9 within the 150-200 °C range correspond to the maximum rate of weight gain produced by oxygen insertion causing Fe 2+ oxidation to Fe 3+ , for which the corresponding temperature, appearing at 164 °C in the metal-free Fe3O4 increases in the noble metal-containing The Pd incorporation on Fe 3 O 4 leads to nanocomposite materials presenting a reduction temperature lower than the pristine magnetite-based substrate, either for the one-step reduction from minority Fe 2 O 3 phases to Fe 3 O 4 or the two-step reduction from Fe 3 O 4 to FeO and Fe 0 . Thus, the reduction temperature for the minor Fe 2 O 3 phases moves bellow 200 • C, in agreement with previous publications employing Pd or other noble metals, such as Au, on Fe 2 O 3 [80,82]. In Figure 8a, it can be observed that the corresponding weight loss for (Ag)Pd-Fe 3 O 4 catalysts starts already at 100 • C, while the beginning of the equivalent loss for the pristine substrate delays until 200 • C.…”
Section: Discussionsupporting
confidence: 91%
“…The first negative peaks observed in Figure 9 within the 150-200 °C range correspond to the maximum rate of weight gain produced by oxygen insertion causing Fe 2+ oxidation to Fe 3+ , for which the corresponding temperature, appearing at 164 °C in the metal-free Fe3O4 increases in the noble metal-containing The Pd incorporation on Fe 3 O 4 leads to nanocomposite materials presenting a reduction temperature lower than the pristine magnetite-based substrate, either for the one-step reduction from minority Fe 2 O 3 phases to Fe 3 O 4 or the two-step reduction from Fe 3 O 4 to FeO and Fe 0 . Thus, the reduction temperature for the minor Fe 2 O 3 phases moves bellow 200 • C, in agreement with previous publications employing Pd or other noble metals, such as Au, on Fe 2 O 3 [80,82]. In Figure 8a, it can be observed that the corresponding weight loss for (Ag)Pd-Fe 3 O 4 catalysts starts already at 100 • C, while the beginning of the equivalent loss for the pristine substrate delays until 200 • C.…”
Section: Discussionsupporting
confidence: 91%
“…These can be assigned to PdO and metallic Pd respectively, which indicates that PdO can be reduced easily at lower temperature, in agreement with other reports. 38 The peaks of PdO and metallic Pd are also observed in the catalyst reduced at 200 C at the Pd 3d 5/2 BEs of 336.9 eV and 335.2 eV. The slightly shi to lower BE value compared with that in the 100 C reduced catalyst may be caused by the increased particle size, 44 as evidenced by XRD and TEM results.…”
Section: Resultsmentioning
confidence: 83%
“…The low BET surface area of reduced samples may be caused by sintering or blocking by metal particles on the support. 38 Fig . 2 exhibits the XRD patterns of the as-prepared Pd-Fe/ Al 2 O 3 catalyst and catalysts aer various treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The promising solution relies on the use of appropriate catalysts and elevated temperatures (80-120 °C, if necessary) [1,9]. The general principle of designing a catalyst is to reduce the size of catalyst nanoparticles to maximize their surface area, simultaneously increasing their catalytic activity and lowering the usage of catalyst materials (in particular precious metals) [10,11]. In this work, we introduce highly dispersed RuOOH nanoparticles (NPs) with sizes of 2-3 nm that are synthesized through the simple hydrolysis of Ru(III) salt as a unique catalyst for selective aerobic oxidation of benzyl alcohol (BzOH) to benzylaldehyde (BzAD).…”
Section: Introductionmentioning
confidence: 99%